Case Report: A rare case of giant ascending aortic dissecting aneurysm requiring redo sternotomy for rescue - Wang, Biao; Wang, Qi; Ma, Zengshan; Zhao, Xin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHere, we report a rare case of a 45-year-old female with a giant ascending aortic dissecting aneurysm (diameter >10 cm) who underwent a redo sternotomy for rescue.MethodsThe patient had aortic coarctation repair and mechanical aortic valve replacement 20 years earlier. Although the patient had significant surgical risks due to a low hemoglobin level and long-term warfarin use, urgent surgical intervention was deemed necessary. The surgery involved cannulating the femoral artery and vein, splitting the sternum, and carefully dissecting the aneurysm. A 23-mm valve conduit was implanted, and the left coronary ostium was transplanted. The right coronary ostium was anastomosed using the Cabrol technique.ResultsThe surgery was successful, with a total operative time of 4 h and 25 min, cardiopulmonary bypass time of 143 min, and aortic cross-clamp time of 78 min. Postoperatively, the patient experienced frequent episodes of cardiac arrest, which resolved with the implantation of a temporary pacing device. Postoperative imaging showed satisfactory results, and the patient was discharged on the ninth postoperative day.ConclusionThis case reports the successful management of a complex and high-risk surgical scenario and provides valuable insight for similar cases.